Effect of LD Slag and Copper Slag as Sand Replacement on Self-Sensing Properties of Cementitious Composites - Raizada, Achleshwar Singh (My University, 2024)
The abstract of the thesis "Effect of LD Slag and Copper Slag as Sand Replacement on Self-Sensing Properties of Cementitious Composites” investigates the possibility of using copper slag and LD slag as conductive fillers in cement mortar. The study aims to improve the electrical and mechanical properties of cementitious composites by adding these industrial by- products. Copper slag, a by-product of the copper smelting process, is known for its excellent mechanical and conductivity qualities, making it an ideal filler. LD slag, a by-product of the steel making process, has significant concentrations of calcium oxide and other inorganic components, which contribute to its cementitious qualities. The study investigates the effects of various materials on workability, compressive strength, and flexural strength, electrical and piezoelectric properties of cement mortar. Furthermore, the research involves microstructural characterization using SEM to better understand the interaction between the fillers and the cement matrix. The findings indicate that the addition of copper slag and LD slag may significantly improve the electrical and mechanical performance of cement mortar, giving a sustainable and cost-effective choice for the construction sector. The study highlights the potential of these by-products in substituting natural resources such as river sand, therefore resolving environmental concerns and improving the use of waste materials in construction. This concludes with recommendations for future research to improve the usage of these components in cementitious composites.
Keywords: Self-Sensing cementitious composite; Bulk form; Copper Slag; LD Slag